2004
DOI: 10.1152/japplphysiol.00194.2004
|View full text |Cite
|
Sign up to set email alerts
|

Geldanamycin treatment inhibits hemorrhage-induced increases in KLF6 and iNOS expression in unresuscitated mouse organs: role of inducible HSP70

Abstract: The aim of this study was to determine whether hemorrhage affects the levels of a variety of stress-related proteins and whether changes can be inhibited by drugs reported to provide protection from ischemia and reperfusion injury. Male Swiss Webster mice were subjected to a 40% hemorrhage without resuscitation. Western blot analysis indicated that c-Jun (an AP-1 protein), Kruppel-like factor 6 (KFL6), and inducible nitric oxide synthase (iNOS) were upregulated sequentially in that order. Pretreatment of mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(81 citation statements)
references
References 39 publications
7
71
3
Order By: Relevance
“…Heidbreder et al [24] suggested that HIF-3α may contribute to protection during early periods of hypoxia and/or moderate hypoxia. In contrast, HIF-1α may confer protection against severe and/or prolonged hypoxia [3,24]. Our experiments did not find that Cell Research | www.cell-research.com…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Heidbreder et al [24] suggested that HIF-3α may contribute to protection during early periods of hypoxia and/or moderate hypoxia. In contrast, HIF-1α may confer protection against severe and/or prolonged hypoxia [3,24]. Our experiments did not find that Cell Research | www.cell-research.com…”
Section: Discussioncontrasting
confidence: 76%
“…Low cellular oxygen tension is seen in pathological conditions including ischemia [1], inflammation [2], hemorrhage [3] and neoplasm [4]. A variety of systemic and cellular responses for homeostatic adaptations are provoked under these hypoxic conditions, including erythropoiesis, vasodilatation, angiogenesis and glycolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Sham-treated mouse organs displayed no changes in the basal levels of c-JUN, KLF6, and iNOS. In addition to changes in this series of stress-related proteins listed above, hemorrhage also increases cellular caspase-3 activity [14], reduces cellular ATP levels [14][15][16][17][18], and elevated mRNA of p38-MAPK, p53, and Bcl-2 [18]. Fig.…”
Section: Effects Of Hemorrhagic Shockmentioning
confidence: 93%
“…A full time-course study of the effect of hemorrhage on a series of stress-related proteins such as c-JUN, Kruppellike factor 6 (KLF6), iNOS, HSP-70i, and hypoxia inducible factor 1α (HIF-1α) has been reported in a hemorrhage mouse model [13]. Based on Western blot data obtained from mouse lung, jejunum, heart, kidney, liver, and brain, c-JUN, KLF6, iNOS, HSP-70i, and HIF-1α are up-regulated (Fig.…”
Section: Effects Of Hemorrhagic Shockmentioning
confidence: 99%
See 1 more Smart Citation